2006
DOI: 10.1111/j.1365-2958.2006.05116.x
|View full text |Cite
|
Sign up to set email alerts
|

The RNA polymerase‐binding protein RbpA confers basal levels of rifampicin resistance on Streptomyces coelicolor

Abstract: SummaryRbpA is an RNA polymerase-binding protein that occurs in the actinomycete family of bacteria and is regulated by the disulphide stress-response sigma factor, σ σ σ σ R , in Streptomyces coelicolor . Here we demonstrate that rbpA null mutants exhibit a slow-growth phenotype and are particularly sensitive to the transcription inhibitor rifampicin. Strikingly, transcription mapping experiments revealed that rbpA expression is induced upon exposure of S. coelicolor to rifampicin and that this, in part, invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 50 publications
3
77
0
Order By: Relevance
“…Both RbpA and CarD are essential transcription activators in Mtb (10,12). CarD is associated with essentially all σ A promoters in Mycobacterium smegmatis in vivo (13), and results suggest that RbpA also likely functions at most, if not all, housekeeping σ-dependent promoters in vivo (11,15). Therefore, it seems likely that RbpA and CarD may function simultaneously on the same RNAP-promoter complexes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Both RbpA and CarD are essential transcription activators in Mtb (10,12). CarD is associated with essentially all σ A promoters in Mycobacterium smegmatis in vivo (13), and results suggest that RbpA also likely functions at most, if not all, housekeeping σ-dependent promoters in vivo (11,15). Therefore, it seems likely that RbpA and CarD may function simultaneously on the same RNAP-promoter complexes.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, it has emerged that the regulation of transcription initiation in the Actinobacteria phylum, which includes major pathogens, such as Mycobacterium tuberculosis (Mtb), and antibiotic producers, such as Streptomyces spp., is distinct from the Eco system by the dependence on two initiation factors, CarD and RbpA, neither of which is found in Eco (10)(11)(12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Orthologues of this protein are only found in actinomycetes. Recently, it was shown that this gene is also induced by rifamicin, and that RbpA is able to stimulate the expression of the rRNA operon even in the presence of rifamicin, conferring a basal level of resistance to this drug (Newell et al, 2006). In M. tuberculosis, Rv2050 was shown to be under the transcriptional control of SigH (SigR orthologue) and upregulated after heat shock and disulfide stress (Manganelli et al, 2002).…”
Section: Resultsmentioning
confidence: 99%